The changing urban political order and politics of space: a study of Hong Kong's POSPD policy - Yu, Yang (2018)
There is an increasing tension between the land development regime and grassroots antigrowth coalitions in Hong Kong, where public spaces have played a critical role. This article aims to examine (1) whether the transitional process of urban political orders is punctuated or gradual; (2) whether transitional change is driven by exogenous factors, endogenous factors, or both; (3) the extent to which the social production model of power is still applicable in the postindustrial era; and (4) how political sociospatial dialectic works in the changing urban political order. This study first reviews the development of Public Open Spaces in Private Development (POSPD) with the changing urban political order, and then explains why POSPD policy has become the concern of both the regime and the emerging antigrowth coalition. Two representative spatial protests are explored to illustrate how awakening civil power challenges the regime and how the regime resists and defends its realm. - Reproduced.
Keywords: Land development - Hong Kong